Membaca kepenyairan Rendra - Haryono, Edi ([Yogyakarta] : Kepel Press, 2005)
Literary criticism on Rendra's works; collection of clippings published previously in Indonesian magazines and newspapers
Keywords: Rendra, W. S. -- 1935-; Indonesian poetry -- History and criticism